PROTOCOL: A comparison of the effectiveness of cognitive behavioural interventions based on delivery features for elevated symptoms of depression in adolescents. Issue 1 (7th January 2020) - Bjornstad, Gretchen J.; Sonthalia, Shreya; Rouse, Benjamin; Timmons, Luke; Whybra, Laura; Axford, Nick
Abstract: This is the protocol for a Campbell review. The primary aim is to estimate the relative efficacy of different modes of CBT delivery compared with control conditions for reducing depressive symptoms in adolescents. The secondary aim is to compare the different modes of delivery with regards to intervention completion/attrition (used as a proxy for intervention acceptability). The review will provide relative effect estimates and ranking probabilities for each outcome based on intervention delivery.